Amorphization dependent recrystallisation of Sb2Te3 - Nur Qalishah Adanan; Simon Wredh; Joel K W Yang; Robert E Simpson (JPhys Materials)
Understanding state-dependent crystallisation kinetics is important for the modelling and design of phase change material (PCM)—based devices, such as multi-level switches. We show how the level of amorphousness (disorder) of antimony-telluride (Sb _2 Te _3 ) can be controlled using pulsed laser heating, and that the recrystallisation temperature strongly depends on the local atomic configurations in the amorphous structure. Indeed, when Sb _2 Te _3 is amorphized with higher laser powers, its subsequent recrystallisation temperature increases by up to 23 °C yet, and counterintuitively the recrystallisation activation energy decreases. This leads to shorter minimum recrystallisation times. This effect is important because it provides a means to switch PCM devices at higher rates through a catalyst-like effect. The optical properties of Sb _2 Te _3 can be gradually tuned by the level of crystallographic disorder. The amorphousness of PCMs provides a further degree-of-freedom to achieve multi-level programmability and tune the switching energy of devices.